An early-strength low-carbon slag cement-based material and its preparation method and application

By using hydration accelerators formed by copper hydroxyl iodate and aluminum dihydrogen phosphate in slag cement, the alkalinity of the cement system and accelerate the hydration reaction are adjusted, and the problem of low hydration in early stages of slag cement is solved, achieving the goal of significant improvement in early strength and low carbon and environmental protection.

CN119241196BActive Publication Date: 2025-02-28SHANDONG LONGFEI ADDITIVES CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411769054.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-28
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The low early hydration degree of slag cement leads to its low early strength, affecting the initial load-bearing capacity and construction progress of the building structure.

Method used

The hydration accelerator formed by copper hydroxyiodate and aluminum dihydrogen phosphate is used to adjust the alkalinity of the cement system through a dual-swap complexation reaction, accelerate the dissolution and hydration reaction of the ore powder to form AFT and C-S-H gels, and improve the compactness of the hydrated products.

Benefits of technology

It significantly improves the early hydration degree and strength of slag cement, solves the problem of insufficient strength in the early stage, and reduces CO2 emissions, utilizes industrial solid waste, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241196B_ABST
    Figure CN119241196B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of slag cement-based materials, and specifically discloses an early-strength low-carbon slag cement-based material, a preparation method and an application thereof. The cement-based material comprises the following components: 60 to 80 parts by weight of slag powder, 15 to 30 parts by weight of gypsum powder, 3 to 10 parts by weight of cement, 1 to 5 parts by weight of a hydration accelerator, and mixing water. The hydration accelerator is formed by hydroxy copper iodate and dihydrogen aluminum phosphate in a mass ratio of 0.08 to 0.13:1. The ratio of the mixing water to the total mass of slag, gypsum and cement is 0.4 to 0.6:1. The hydration accelerator composed of hydroxy copper iodate and dihydrogen aluminum phosphate in the present invention effectively promotes the early hydration degree of low-carbon slag cement, thereby improving the early strength, while ensuring that the mid- and late-stage strength of the cement will not be significantly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of slag cement-based materials, and in particular to an early-strength low-carbon slag cement-based material and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] The production and use of Portland cement is one of the main sources of global carbon dioxide (CO2) emissions. In the cement production process, CO2 emissions mainly come from two aspects: one is the decomposition of carbonate raw materials during calcination, and the other is the combustion of fossil fuels. In order to cope with global climate change, reducing CO2 emissions in the cement industry has become an important way.

[0004] Slag cement, especially Portland slag cement, has been widely used in construction and engineering due to its advantages such as stable setting time, stable strength and low hydration heat. However, the early hydration degree of low-carbon slag cement is relatively low, resulting in its low early strength. This is mainly because the hydration reaction rate of slag cement is slow and it takes longer to develop its strength. In addition, the hydration of slag cement is also affected by factors such as ambient temperature, humidity and cement particle fineness, all of which affect the development of the early strength of slag cement.

[0005] Insufficient early strength development of slag cement will lead to insufficient initial bearing capacity of the building structure, affecting the safety and reliability of the project. In addition, it will also delay the construction progress because it takes longer to wait for the slag cement to undergo hydration reaction to increase strength. Therefore, it is very important to improve the early hydration degree of slag cement and thus improve its early strength. Summary of the invention

[0006] In view of the above problems, the present invention provides an early-strength low-carbon slag cement-based material and a preparation method and application thereof, which can effectively improve the early hydration degree of slag cement and significantly improve the early strength. Specifically, the technical solution of the present invention is as follows.

[0007] In the first aspect of the present invention, an early strength low carbon slag cement-based material is disclosed, wherein the raw materials include the following components: 60-80 parts by weight of slag powder, 15-30 parts by weight of gypsum powder, 3-10 parts by weight of cement, 1-5 parts by weight of hydration accelerator, and mixing water. The hydration accelerator is formed by iodic acid copper hydroxide Cu(IO3)2·3Cu(OH)2 and dihydrogen aluminum phosphate (Al(H2PO4)3) in a mass ratio of 0.08-0.13:1. The ratio of the mixing water to the total mass of slag, gypsum, and cement is 0.4-0.6:1.

[0008] Furthermore, the mass ratio of the main components (expressed in the form of oxides) in the slag powder is CaO:SiO2:Al2O3:MgO:Fe2O3:SO3:TiO2=32~36:25~40:15~20:5~10:0.1~0.5:2~3:1~2.

[0009] Furthermore, the slag powder is graded from powders of 400-500 mesh, 500-600 mesh, 600-700 mesh, and 700-800 mesh. Optionally, the mass ratio of the powders of 400-500 mesh, 500-600 mesh, 600-700 mesh, and 700-800 mesh is 15-20:53-60:10-20:7-10. The above-mentioned slag powder can give full play to the micro-aggregate effect, making the structure of the cement-based material more compact, and helping to improve its strength and durability.

[0010] Furthermore, the cement includes at least one of silicate cement, benchmark cement, sulphoaluminate cement, high-belite sulphoaluminate cement and the like.

[0011] Furthermore, the gypsum powder includes anhydrous gypsum and dihydrate gypsum. Optionally, the mass ratio of the anhydrous gypsum to the dihydrate gypsum is 0.3-0.6:1. The above-mentioned composite gypsum can react with alkali in cement to form stable calcium sulfate to improve the alkali-aggregate reaction of cement and reduce its adverse effects on mechanical properties.

[0012] Furthermore, the early strength low carbon slag cement-based material also includes aggregates. Optionally, the ratio of the aggregates to the total mass of slag, gypsum and cement is 2.5-3.5:1.

[0013] Furthermore, the early strength low carbon slag cement-based material also includes at least one of a polycarboxylic acid water reducer, a naphthalene water reducer, and a melamine water reducer. Optionally, the ratio of the water reducer to the total mass of slag, gypsum, and cement is 0.003-0.005:1.

[0014] In a second aspect of the present invention, a method for preparing the early-strength low-carbon slag cement-based material is disclosed, comprising the following steps:

[0015] (1) Add the hydration accelerator to the mixing water and stir evenly. The resulting mixed solution is ready for use.

[0016] (2) The slag, gypsum and cement are mixed evenly to obtain a ternary cementitious material. Then the mixed liquid is added and mixed evenly to obtain the early strength low carbon slag cement-based material.

[0017] Furthermore, step (2) further includes the step of adding the above-mentioned aggregate and water reducing agent into the ternary cementitious material, and then adding the mixed liquid after completion.

[0018] In the third aspect of the present invention, the application of the early-strength low-carbon slag cement-based material in construction projects, bridge projects, road projects, airport runways, curbstones, crash barriers, carbon-fixing bricks, etc. is disclosed.

[0019] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects:

[0020] As mentioned above, although slag cement has lower carbon emissions, the early hydration degree of this cement material is low, which leads to low early strength. To this end, a hydration accelerator formed by hydroxycopper iodate and dihydrogen aluminum phosphate is added to the slag cement-based material of the present invention, which significantly improves the early hydration degree of slag cement and significantly improves the early strength of cement. This is because:

[0021] (1) The copper iodate hydroxide and aluminum dihydrogen phosphate undergo a double displacement complexation reaction (Cu 2+ +2IO 3− +Al 3+ +3PO4 3− →Cu(IO3)2+Al(PO4)3). On the one hand, the formation of the complex product adjusts the alkalinity of the cement system, accelerates the dissolution of the mineral powder, and the dissolved silicon-aluminum phase reacts with gypsum to form AFT and CSH gels, which can significantly improve the early strength of slag cement-based materials. On the other hand, the formed complex fills the hydration product layer of the slag cement system, reduces the layer porosity of the hydration product, thereby improving the compactness of the hydration product and promoting the improvement of cement strength.

[0022] (2) The hydroxycopper iodate in the hydration accelerator is alkaline, which helps to improve the dissolution of the gypsum. The dissolved gypsum reacts with the silicon-aluminum phase in the slag to form AFt and CSH gel, which also helps to improve the early strength. At the same time, the aluminum ions in the aluminum dihydrogen phosphate can also promote the hydration of C2S and C3S in the cement, thereby promoting the early hydration degree of cement, forming more CSH gel, and improving the early strength of slag cement-based materials. At the same time, the phosphate in the aluminum dihydrogen phosphate can also react with the silicate and calcium ions in the CSH gel to form phosphate compounds, making the structure of the CSH gel more compact, thereby improving the full-age strength and durability of the slag cement-based material. In addition, the phosphate provided by the aluminum dihydrogen phosphate in the hydration accelerator can also react with the calcium ions released by the hydration reaction of the slag powder to form calcium phosphate. At the same time, the phosphate can also react with unhydrated slag and cement clinker to form new phosphorus-containing compounds, making the structure of the hydration products of the slag and cement more compact, and also helping to improve the strength and durability of slag cement-based materials throughout their age.

[0023] In summary, the slag cement-based material of the present invention not only overcomes the problem of low early strength due to low early hydration degree, but also effectively reduces CO2 emissions compared to silicate cement. At the same time, the utilization of industrial solid wastes such as slag and gypsum helps to reduce environmental pollution caused by their stacking. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0025] Figure 1 This is a sample diagram of the mixed solution formed by the hydration accelerator and mixing water of the following Example 1.

[0026] Figure 2 The following is a compressive strength test diagram of Example 1. DETAILED DESCRIPTION

[0027] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0028] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions.

[0029] In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The technical solution of the present invention is further described in conjunction with the accompanying drawings and specific embodiments.

[0030] Example 1

[0031] A method for preparing an early-strength low-carbon slag cement-based material comprises the following steps:

[0032] (1) Weigh the raw material components according to the following proportions: 70 parts by weight of slag powder, 20 parts by weight of gypsum powder, 5 parts by weight of 42.5 ordinary Portland cement, 5 parts by weight of hydration accelerator, 285 parts of river sand fine aggregate, and 46 parts by weight of mixing water. Wherein: the mass ratio of the main components (expressed in the form of oxides) in the slag powder is CaO: SiO2: Al2O3: MgO: Fe2O3: SO3: TiO2 = 34: 30: 18: 7: 0.3: 2.5: 1.5, and the slag powder is graded with powders of 400 mesh, 500 mesh, 600 mesh, and 700 mesh in a mass ratio of 20: 55: 15: 10. The hydration accelerator is a mixture of iodic acid hydroxy copper and dihydrogen aluminum phosphate in a mass ratio of 0.1: 1. The gypsum powder is a mixture of anhydrous gypsum and dihydrate gypsum in a mass ratio of 0.5: 1, and its fineness is 300 mesh.

[0033] (2) Add the hydration accelerator in step (1) to the mixing water and stir evenly to obtain a mixed solution for use. Figure 1 shown.

[0034] (3) The slag, gypsum powder and 42.5 ordinary Portland cement are mixed and stirred evenly to obtain a ternary cementitious material. Then, the river sand and fine aggregate are added and stirred continuously to mix the raw materials evenly. Finally, the mixed liquid of step (2) is added and stirred slowly for 120 seconds at a rotation rate of 140 r / min and a revolution rate of 60 r / min. After stopping stirring for 15 seconds, the mixture is stirred quickly for 120 seconds at a rotation rate of 500 r / min and a revolution rate of 300 r / min to obtain a slag cement-based material.

[0035] Performance test: According to GB / T 17671-2021 "Test method for strength of cement mortar (ISO method)", the early (3d), mid-term (7d), and late (28d) compressive strength of the slag cement-based material prepared in this embodiment are tested. The test process is as follows: Figure 2 The test results are shown in Table 1 below:

[0036] Table 1 Compressive strength test results

[0037] .

[0038] Example 2

[0039] A method for preparing an early-strength low-carbon slag cement-based material comprises the following steps:

[0040] (1) Weigh the raw material components according to the following proportions: 80 parts by weight of slag powder, 15 parts by weight of gypsum powder, 3 parts by weight of sulphoaluminate cement, 2 parts by weight of hydration accelerator, 343 parts by weight of river sand fine aggregate, 58.8 parts by weight of mixing water, and 0.294 parts by weight of polycarboxylate water reducer. The mass ratio of the main components (expressed in the form of oxides) in the slag powder is CaO: SiO2: Al2O3: MgO: Fe2O3: SO3: TiO2 = 32: 25: 15: 5: 0.1: 2: 1, and the slag powder is graded with powders of 500 mesh, 600 mesh, 700 mesh, and 800 mesh in a mass ratio of 15: 53: 10: 7. The hydration accelerator is a mixture of hydroxycopper iodate and dihydrogen aluminum phosphate in a mass ratio of 0.08: 1. The gypsum powder is prepared by mixing anhydrous gypsum and dihydrate gypsum in a mass ratio of 0.3:1, and has a fineness of 300 meshes.

[0041] (2) Add the hydration accelerator in step (1) to the mixing water and stir evenly to obtain a mixed solution for later use.

[0042] (3) The slag, gypsum powder and sulphoaluminate cement are mixed and stirred evenly to obtain a ternary cementitious material. Then, the river sand fine aggregate and the water reducing agent are added and stirred continuously to make the raw materials evenly mixed. Finally, the mixed solution of step (2) is added and stirred slowly for 120 seconds at a rotation rate of 140 r / min and a revolution rate of 60 r / min. After stopping stirring for 15 seconds, the mixture is stirred rapidly for 120 seconds at a rotation rate of 500 r / min and a revolution rate of 300 r / min to obtain a slag cement-based material.

[0043] Performance test: According to GB / T 17671-2021 "Test method for strength of cement mortar (ISO method)", the early (3d), mid-term (7d), and late (28d) compressive strength of the slag cement-based material prepared in this embodiment were tested. The test results are shown in Table 2 below:

[0044] Table 2 Compressive strength test results

[0045] .

[0046] Example 3

[0047] A method for preparing an early-strength low-carbon slag cement-based material comprises the following steps:

[0048] (1) Weigh the raw material components according to the following proportions: 60 parts by weight of slag powder, 30 parts by weight of gypsum powder, 10 parts by weight of 42.5 ordinary Portland cement, 1 part by weight of hydration accelerator, 250 parts by weight of river sand fine aggregate, 40 parts by weight of mixing water, and 0.5 parts by weight of naphthalene-based water reducer. The mass ratio of the main components (expressed in the form of oxides) in the slag powder is CaO: SiO2: Al2O3: MgO: Fe2O3: SO3: TiO2 = 36: 40: 20: 10: 0.5: 3: 2, and the slag powder is graded with powders of 400 mesh, 550 mesh, 600 mesh, and 700 mesh in a mass ratio of 18: 60: 20: 9. The hydration accelerator is a mixture of hydroxycopper iodate and dihydrogen aluminum phosphate in a mass ratio of 0.13: 1. The gypsum powder is prepared by mixing anhydrous gypsum and dihydrate gypsum in a mass ratio of 0.6:1, and has a fineness of 200 meshes.

[0049] (2) Add the hydration accelerator in step (1) to the mixing water and stir evenly to obtain a mixed solution for use.

[0050] (3) The slag, gypsum powder and 42.5 ordinary Portland cement are mixed and stirred evenly to obtain a ternary cementitious material. Then, the river sand fine aggregate and water reducer are added and stirred continuously to mix the raw materials evenly. Finally, the mixed solution of step (2) is added and stirred slowly for 120 seconds at a rotation rate of 140 r / min and a revolution rate of 60 r / min. After stopping stirring for 15 seconds, the mixture is stirred quickly for 120 seconds at a rotation rate of 500 r / min and a revolution rate of 300 r / min to obtain a slag cement-based material.

[0051] Performance test: According to GB / T 17671-2021 "Test method for strength of cement mortar (ISO method)", the early (3d), mid-term (7d), and late (28d) compressive strength of the slag cement-based material prepared in this embodiment were tested. The test results are shown in Table 3 below:

[0052] Table 3 Compressive strength test results

[0053] .

[0054] Example 4

[0055] A method for preparing an early-strength low-carbon slag cement-based material comprises the following steps:

[0056] (1) Weigh the raw material components according to the following proportions: 70 parts by weight of slag powder, 20 parts by weight of gypsum powder, 5 parts by weight of 42.5 ordinary Portland cement, 285 parts of river sand fine aggregate, and 46 parts by weight of mixing water. The mass ratio of the main components (expressed in the form of oxides) in the slag powder is CaO: SiO2: Al2O3: MgO: Fe2O3: SO3: TiO2 = 34: 30: 18: 7: 0.3: 2.5: 1.5, and the slag powder is graded with powders of 400 mesh, 500 mesh, 600 mesh, and 700 mesh in a mass ratio of 20: 55: 15: 10. The gypsum powder is a mixture of anhydrous gypsum and dihydrate gypsum in a mass ratio of 0.5: 1, and its fineness is 300 mesh.

[0057] (2) The slag, gypsum powder and 42.5 ordinary Portland cement are mixed and stirred evenly to obtain a ternary cementitious material. Then, the river sand and fine aggregate are added and stirred continuously to mix the raw materials evenly. Finally, the mixing water is added and stirred slowly for 120 seconds at a rotation rate of 140 r / min and a revolution rate of 60 r / min. After stopping stirring for 15 seconds, the mixture is stirred quickly for 120 seconds at a rotation rate of 500 r / min and a revolution rate of 300 r / min to obtain a slag cement-based material.

[0058] Performance test: According to GB / T 17671-2021 "Test method for strength of cement mortar (ISO method)", the early (3d), mid-term (7d), and late (28d) compressive strength of the slag cement-based material prepared in this embodiment were tested. The test results are shown in Table 4 below:

[0059] Table 4 Compressive strength test results

[0060] .

[0061] Example 5

[0062] A method for preparing an early-strength low-carbon slag cement-based material comprises the following steps:

[0063] (1) Weigh the raw material components according to the following proportions: 60 parts by weight of slag powder, 30 parts by weight of gypsum powder, 10 parts by weight of 42.5 ordinary Portland cement, 1 part by weight of hydration accelerator, 250 parts by weight of river sand fine aggregate, 40 parts by weight of mixing water, and 0.5 parts by weight of naphthalene-based water reducer. The mass ratio of the main components (expressed in the form of oxides) in the slag powder is CaO: SiO2: Al2O3: MgO: Fe2O3: SO3: TiO2 = 36: 40: 20: 10: 0.5: 3: 2, and the slag powder is graded with powders of 400 mesh, 550 mesh, 600 mesh, and 700 mesh in a mass ratio of 18: 60: 20: 9. The hydration accelerator is aluminum dihydrogen phosphate. The gypsum powder is a mixture of anhydrous gypsum and dihydrate gypsum in a mass ratio of 0.6: 1, and its fineness is 200 mesh.

[0064] (2) Add the hydration accelerator in step (1) to the mixing water and stir evenly to obtain a mixed solution for later use.

[0065] (3) The slag, gypsum powder and 42.5 ordinary Portland cement are mixed and stirred evenly to obtain a ternary cementitious material. Then, the river sand fine aggregate and water reducer are added and stirred continuously to mix the raw materials evenly. Finally, the mixed solution of step (2) is added and stirred slowly for 120 seconds at a rotation rate of 140 r / min and a revolution rate of 60 r / min. After stopping stirring for 15 seconds, the mixture is stirred quickly for 120 seconds at a rotation rate of 500 r / min and a revolution rate of 300 r / min to obtain a slag cement-based material.

[0066] Performance test: According to GB / T 17671-2021 "Test method for strength of cement mortar (ISO method)", the early (3d), mid-term (7d), and late (28d) compressive strength of the slag cement-based material prepared in this embodiment were tested. The test results are shown in Table 5 below:

[0067] Table 5 Compressive strength test results

[0068] .

[0069] Example 6

[0070] A method for preparing an early-strength low-carbon slag cement-based material comprises the following steps:

[0071] (1) Weigh the raw material components according to the following proportions: 80 parts by weight of slag powder, 15 parts by weight of gypsum powder, 3 parts by weight of sulphoaluminate cement, 2 parts by weight of hydration accelerator, 343 parts by weight of river sand fine aggregate, 58.8 parts by weight of mixing water, and 0.294 parts by weight of polycarboxylate water reducer. The mass ratio of the main components (expressed in the form of oxides) in the slag powder is CaO: SiO2: Al2O3: MgO: Fe2O3: SO3: TiO2 = 32: 25: 15: 5: 0.1: 2: 1, and the slag powder is graded from powders of 500 mesh, 600 mesh, 700 mesh, and 800 mesh in a mass ratio of 15: 53: 10: 7. The hydration accelerator is iodized copper hydroxide. The gypsum powder is a mixture of anhydrous gypsum and dihydrate gypsum in a mass ratio of 0.3: 1, and its fineness is 300 mesh.

[0072] (2) Add the hydration accelerator in step (1) to the mixing water and stir evenly to obtain a mixed solution for use.

[0073] (3) The slag, gypsum powder and sulphoaluminate cement are mixed and stirred evenly to obtain a ternary cementitious material. Then, the river sand fine aggregate and the water reducing agent are added and stirred continuously to make the raw materials evenly mixed. Finally, the mixed solution of step (2) is added and stirred slowly for 120 seconds at a rotation rate of 140 r / min and a revolution rate of 60 r / min. After stopping stirring for 15 seconds, the mixture is stirred rapidly for 120 seconds at a rotation rate of 500 r / min and a revolution rate of 300 r / min to obtain a slag cement-based material.

[0074] Performance test: According to GB / T 17671-2021 "Test method for strength of cement mortar (ISO method)", the early (3d), mid-term (7d), and late (28d) compressive strength of the slag cement-based material prepared in this embodiment were tested. The test results are shown in Table 6 below:

[0075] Table 6 Compressive strength test results

[0076] .

[0077] Example 7

[0078] A method for preparing an early-strength low-carbon slag cement-based material comprises the following steps:

[0079] (1) Weigh the raw material components according to the following proportions: 70 parts by weight of slag powder, 20 parts by weight of anhydrous gypsum powder with a fineness of 300 mesh, 5 parts by weight of 42.5 ordinary Portland cement, 5 parts by weight of hydration accelerator, 285 parts of river sand fine aggregate, and 46 parts by weight of mixing water. The mass ratio of the main components (expressed in the form of oxides) in the slag powder is CaO: SiO2: Al2O3: MgO: Fe2O3: SO3: TiO2 = 34: 30: 18: 7: 0.3: 2.5: 1.5, and the slag powder is graded with powders of 400 mesh, 500 mesh, 600 mesh, and 700 mesh in a mass ratio of 20: 55: 15: 10. The hydration accelerator is a mixture of hydroxycopper iodate and dihydrogen aluminum phosphate in a mass ratio of 0.1: 1.

[0080] (2) Add the hydration accelerator in step (1) to the mixing water and stir evenly to obtain a mixed solution for use.

[0081] (3) The slag, anhydrous gypsum powder and 42.5 ordinary Portland cement are mixed and stirred evenly to obtain a ternary cementitious material. Then, the river sand and fine bones are added and stirred continuously to mix the raw materials evenly. Finally, the mixed liquid of step (2) is added and stirred slowly for 120 seconds at a rotation rate of 140 r / min and a revolution rate of 60 r / min. After stopping stirring for 15 seconds, the mixture is stirred quickly for 120 seconds at a rotation rate of 500 r / min and a revolution rate of 300 r / min to obtain a slag cement-based material.

[0082] Performance test: According to GB / T 17671-2021 "Test method for strength of cement mortar (ISO method)", the early (3d), mid-term (7d), and late (28d) compressive strength of the slag cement-based material prepared in this embodiment were tested. The test results are shown in Table 7 below:

[0083] Table 7 Compressive strength test results

[0084] .

[0085] The above is only an illustrative solution of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An early strength low carbon slag cement-based material, characterized in that: The components include: 60-80 parts by weight of slag powder, 15-30 parts by weight of gypsum powder, 3-10 parts by weight of cement, 1-5 parts by weight of hydration accelerator, and mixing water; wherein: The hydration accelerator is formed by hydroxycopper iodate and aluminum dihydrogen phosphate in a mass ratio of 0.08-0.13:1; The ratio of the mixing water to the total mass of slag powder, gypsum powder and cement is 0.4-0.6:

1.

2. The early strength low carbon slag cement-based material according to claim 1, characterized in that: Expressed in the form of oxides, the mass ratio of the main components in the slag powder is CaO:SiO2:Al2O3:MgO:Fe2O3:SO3:TiO2=32~36:25~40:15~20:5~10:0.1~0.5:2~3:1~2.

3. The early strength low carbon slag cement-based material according to claim 1, characterized in that: The slag powder is graded from powders with finenesses of 400-500 mesh, 500-600 mesh, 600-700 mesh, and 700-800 mesh.

4. The early strength low carbon slag cement-based material according to claim 3, characterized in that: The mass ratio of the powders of 400-500 mesh, 500-600 mesh, 600-700 mesh, and 700-800 mesh is 15-20:53-60:10-20:7-10.

5. The early strength low carbon slag cement-based material according to claim 1, characterized in that: The cement comprises at least one of silicate cement, standard cement, sulphoaluminate cement and high-belite sulphoaluminate cement.

6. The early strength low carbon slag cement-based material according to claim 1, characterized in that: The gypsum powder includes anhydrous gypsum and dihydrate gypsum.

7. The early strength low carbon slag cement-based material according to claim 6, characterized in that: The mass ratio of the anhydrous gypsum to the dihydrate gypsum is 0.3-0.6:

1.

8. The early strength low carbon slag cement-based material according to any one of claims 1 to 7, characterized in that: Also includes aggregates.

9. The early strength low carbon slag cement-based material according to claim 8, characterized in that: The ratio of the aggregate to the total mass of slag powder, gypsum powder and cement is 2.5-3.5:

1.

10. The early strength low carbon slag cement-based material according to any one of claims 1 to 7, characterized in that: The early strength low carbon slag cement-based material also includes at least one of a polycarboxylic acid water reducer, a naphthalene water reducer and a melamine water reducer.

11. The early strength low carbon slag cement-based material according to claim 10, characterized in that: The ratio of the water reducing agent to the total mass of slag powder, gypsum powder and cement is 0.003-0.005:

1.

12. The method for preparing the early strength low carbon slag cement-based material according to any one of claims 1 to 11, characterized in that: The steps include: (1) Add the hydration accelerator to the mixing water and stir evenly to obtain a mixed solution for use; (2) The slag powder, gypsum powder and cement are mixed evenly to obtain a ternary cementitious material; and then the mixed liquid is added and mixed evenly to obtain the early strength low carbon slag cement-based material; Alternatively, step (2) further comprises the step of adding aggregates from the early strength low carbon slag cement-based material according to claim 8 or 9 and / or a water reducing agent from the early strength low carbon slag cement-based material according to claim 10 or 11 to the ternary cementitious material, and then adding the mixed liquid after completion.

13. Use of the early-strength low-carbon slag cement-based material according to any one of claims 1 to 11, or the early-strength low-carbon slag cement-based material obtained by the preparation method according to claim 12 in construction engineering, bridge engineering, and road engineering.

Citation Information

Patent Citations

  • Concrete compound type chloride-free early strength agent and preparation method thereof

    CN105198273A

  • Heat-resistant concrete cementing material as well as preparation method and application thereof

    CN115368037A